A Study On Superior-Subordinate Attribution Dereferences - Tan, Chun Sheng (1996)
How superiors and subordinates attribute the subordinate's performance has long been a widely studied field. One of the basic principles of the Theory of Attribution as proposed by llcidcr (1958) is that there arc bound to be differences between the attribution by the superior and the attribution n1ade by the subordinate. The purpose of this study is to detern1ine whether the quality of communication and the social distance between the superior and subordinate play an important role in determining the degree of difference in the attributions 1nade by the superior and subordinate on the subordinate's performance.